ARF: the most misunderstood GTPase I ever knew - why study ARF GAPs - Turn, Rachel E.; Dacks, Joel Bryan; Rosenberg, Eric M.; Soubias, Olivier; Northup, John K.; Randazzo, Paul A. (Frontiers in Molecular Biosciences, 2025)
ADP-ribosylation factors (ARFs) are GTP-binding proteins that were discovered in the early 1980s, shortly after heterotrimeric GTP-binding proteins (G proteins) and nearly simultaneously with RAS. G proteins formed the basis for the signaling paradigm that has been broadly applied to GTPases, including both RAS and ARF. In this paradigm, GTP-binding proteins act as switches. When converted from the GDP-bound form to the GTP-bound form, GTPases bind effector proteins to transduce a signal. This paradigm is consistent, at least in part, with RAS function as RAS•GTP activates effectors to drive cellular responses such as proliferation. ARF, on the other hand, functions outside this paradigm, at least in its first discovered physiological role: regulation of membrane traffic. Nevertheless, ARFs are often generalized as “on” and “off” switches controlling signaling pathways. In this study, we (i) briefly describe the history of the discoveries of three families of GTPases to provide an understanding of the genesis of the G-protein signaling model, (ii) enumerate some key differences between ARFs, RAS, and G proteins (which better fit the paradigm of molecular switches), and (iii) describe an alternate model for ARFs, in which their cycling between GTP binding and hydrolysis mediates cellular activities, rather than ARFs acting as mediators in a signaling cascade. Furthermore, we highlight the key role of GTPase-activating proteins (GAPs) as integral to ARF function.